Strategi Pemasaran Produk Tabungan Easy Mudharabah dalam Meningkatkan Jumlah Nasabah Pada PT Bank Syariah Indonesia KCP Medan Juanda - Miftha Maulida Anggi Natama; Muhammad Lathief Ilhamy Nasution (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
A company's success or failure is determined by the strategy, theory and marketing management applied. This research was conducted to find out what marketing strategies for easy mudharabah savings products are used by Bank Syariah Indonesia KCP Medan Juanda to increase the number of customers. This research uses descriptive qualitative analysis methods, using primary data, namely the researcher took data directly by interviewing the Marketing Funding BSI KCP Medan Juanda and secondary data secondary data obtained from documents, scientific journals, books and literature related to the research problem. The results obtained were that BSI carried out a marketing strategy, one of which was by implementing the 4p marketing mix, namely (product, price, promotion, place). BSI must be able to estimate strategic locations, collaborate with other agencies, expand market share, improve quality and innovate.